SOME PRELIMINARY INVESTIGATIONS OF CANNIBALISM IN MOSQUITO POPULATIONS COLLECTED FROM URBAN AREAS OF DISTRICT SHEIKHPURA, PAKISTAN - AMIN, S; ALEEM, A; REHMAN, A; ARSHAD, S; HUSSAIN, SM; MAAN, NA; MUDASSER, M; AHMAD, M; AYUB, MM; ABDIN, ZU (Biological and Clinical Sciences Research Journal, 2024)
In the population of mosquitoes, there is substantial research documentation on cannibalism between larval stages therefore, in our research work cannibalism in mosquito populations was studied in the laboratory experiments comparing old (third and fourth-instars) and young (first-instar) larvae of the mosquito species occurring dominantly in urban areas of District Sheikhupura. Although mosquitoes can grow in temporary aquatic habitats having wildly varied topologies, the significance of the site shape in which cannibals and victims coexist has not received enough attention from researchers. Then, experimental trials in the containers were performed, and the cannibalism rate was estimated at 24 and 48hrs. The effect of spatial form on cannibalism in mosquito larvae of the A. albopictus species was assessed, adding a new essential element to those influencing ecological interactions in these habitats. Our data reveals that cannibalism was observed mostly between the fully mature and fully immature larvae of the mosquito population and a decline was observed between the mature population. These basic findings of our work would help devise sustainable control strategies for mosquito population (A. albopictus and A. aegypti) etc. in vector management programs.